Successful long-term weight loss among participants with diabetes receiving an intervention promoting an adapted Mediterranean-style dietary pattern: the Heart Healthy Lenoir Project. Issue 1 (29th March 2017) - Embree, Genevieve G R; Samuel-Hodge, Carmen D; Johnston, Larry F; Garcia, Beverly A; Gizlice, Ziya; Evenson, Kelly R; DeWalt, Darren A; Ammerman, Alice S; Keyserling, Thomas C
Abstract : Objective: To examine weight change by diabetes status among participants receiving a Mediterranean-style diet, physical activity, and weight loss intervention adapted for delivery in the southeastern USA, where rates of cardiovascular disease (CVD) are disproportionately high. Research design and methods: The intervention included: Phase I (months 1–6), an individually tailored intervention promoting a Mediterranean-style dietary pattern and increased walking; Phase II (months 7–12), option of a 16-week weight loss intervention for those with BMI≥25 kg/m 2 offered as 16 weekly group sessions or 5 group sessions and 10 phone calls, or a lifestyle maintenance intervention; and Phase III (months 13–24), weight loss maintenance intervention for those losing ≥8 pounds with all others receiving a lifestyle maintenance intervention. Weight change was assessed at 6, 12, and 24-month follow-up. Results: Baseline characteristics (n=339): mean age 56, 77% female, 65% African-American, 124 (37%) with diabetes; mean weight 103 kg for those with diabetes and 95 kg for those without. Among participants with diabetes, average weight change was −1.2 kg (95% CI −2.1 to −0.4) at 6 months (n=92), −1.5 kg (95% CI −2.9 to −0.2) at 12 months (n=96), and −3.7 kg (95% CI −5.2 to −2.1) at 24 months (n=93). Among those without diabetes, weight change was −0.4 kg (95% CI −1.4 to 0.6) at 24 months (n=154). Conclusions: Participants with diabetes experienced sustained weight loss at 24-month follow-up. High-risk US populations with diabetes may experience clinically important weight loss from this type of lifestyle intervention. Trial registration number: NCT01433484.